Economics and Management in the Biopharmaceutical Industry in the USA : Evolution and Strategic Change - Kim, Rachel; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
From a managerial perspective, the biopharmaceutical industry represents a competitive, fast-changing, intellectually-powered, innovation-driven sector. Many management scholars have studied this discontinuous era to make sense of strategic behavior and the cognition of firms and top managers. A past look at the biopharmaceutical industry provides answers to questions that most managers have. For example, what options do you have and what actions do you take when new firms enter your industry? In the 1970s, new biotechnology firms, funded by venture capitalists, appeared in the pharmaceutical industry with new knowledge. Successful pharmaceutical firms decided to collaborate with the new entrants and forge relationships to develop and create new, biotechnology engineered drugs. Thus, the addition of new biotechnology firms ushered in a new business model based on strategic alliances. Strategic alliances have now become an industrial norm called open innovation. The author looks at the historical path of the biopharmaceutical industry, particularly in the United States. While the pharmaceutical industry s main contributions to society are substantial, there are pressing challenges the industry must face, such as an increase in infectious disease outbreaks or the global aging population, which require new types of care, additionally, mental health care and prescription painkiller addiction are persistent issues with economic repercussions to both federal and local governments. This book presents a holistic view of the biopharmaceutical industry, putting it in a historical context. It will best serve those who are eager to learn about this dynamic, fast-evolving industry andwho would like to tackle current biopharmaceutical industry issues in the United States and be prepared for future industry challenges.
Authors Words: Overview of Strategic Management and Corporate Practice in the United States, Chapter 1. Introduction, Main Contributions of the Biopharmaceutical Industry, Current Public Health Issues in the United States, Chapter 2. In the Early Days of thePharmaceutical Industry Worldwide, Aspirin in GermanyandPenicillin from the United Kingdom to the United States, Aspirin Discovery in Bayer, Germany, Penicillin Discovery in the United Kingdom , Pfizerfrom 18491939: Fermentation Innovator, Pfizer in the1940s: Large-Scale Penicillin Manufacturer, Pfizer in the 1950s: New Pharmaceutical Company with Terramycin, Streptomycin Discovery by Waksman and Patented by Merck, Shift from Germany to the United Kingdom and United States: 1950 1960s, Chapter 3. The Birth of Biotechnology , Slow Progress Despite Gene Splicing Technology Breakthrough, Breakthroughs from the Two Collaborators, Fear of the Unknown, The First Patents in theRecombinant DNA Area, Genentech Was Born, Chapter 4. Emergence of Biotechnology Firms in the1970s1990s, Threats of Young Competitors with New Knowledge, New Biotechnology Firms' Emergence in a Social Context: Response of Science Communities, Science Department at UCSF, UC Berkeley, and Stanford, New Biotechnology Firms' Emergence in the Legal Environment, Case Study 1: Genentech, The First Biotechnology Firm , Case Study 2: Amgen, The Second Biotechnology Company, Chapter 5. New Biotechnology Firms' Emergence from a Pharmaceutical Management Perspective, Case Study 3: Eli Lilly's Open Innovation, Early History of Eli Lilly, Case Study 4: Bristol-Myers Squibb (BMS) , Chapter 6. US Regulations on theBiopharmaceutical Industry and Their Impact, Drug Act Amendments of 1962: Scientific Evidence of Safety and Efficacy, Drug Price Competition and Patent Restoration Act of 1984 for Generic Drugs, The Orphan Drug Act of 1983 for Rare Diseases, Off-Label Prescribing Practice, The Prescription Drug User Fee Act (PDUFA) in 1992, Chapter 7. Lawand Strategies: How Biopharmas Strategies Adapted in Response to U.S. Law Changes, Healthcare Spending in the United States: The Economics of Biosimilars, Law Changes Since 2009, Implications of the Biologics Price Competition and Innovation Act (BPCIA) , Biologics: New Business Models, Dogfight 1: AbbVies Humira versus Amgens Amjevita, Dogfight 2: AbbVies Humira versus Samsung Bioepis Co.s Imraldi, Dogfight 3: Johnson & Johnsons Remicade versus Samsungs Renflexis, The Future of Biosimilars, AbbVie: Best Strategist with Innovative Drugs, Generic Brands: Now Very Important Business Models, Chapter 8. Opportunistic Business Models in the Generic Drug Market, Mylan: The Path to Becoming a Giant Generic Drug Company, Unanticipatedly Strong Patents Defense of Bristol Myers Squibb, Turing Pharmaceutical: Too Opportunistic, Yet Legal Business Model, Chapter 9. Low Productivity of Drug Companies, Steep Rising Cost of Drugs as Strict Regulations Occurred, Low Productivity in Terms of New Drugs Approval, Chapter 10. Payers, Purchasers,and Promotions, Who Pays for Medicines in the United States, Direct-To-Consumer Advertising for Medicines, Food and Drug Administration, Case Study 5: The Path of Merck, The Unforgettable Mistake by Merck: Vioxx, Chapter 11. Innovation Capabilities, Innovation from a Dynamic Capabilities Perspective, R&D Capabilities: Patents, Publications, and Alliances, Chapter 12. Immuno-cancer Therapy, Immuno-cancer Therapy: BMS versus Merck, Case Study 6: Gilead Sciences, Inc. , Case Study 7: Kite Pharma, Current Achievements in CAR-T Cell Therapy: Novartis versus. Gilead Sciences, New Business Models for CAR-T Cell Therapies, Chapter 13. The Biopharmaceutical Industry in the Future, High Expectations in Personalized Medicines, Emerging Markets, The Impact of Visionary and Strategic Leadership, New Business Models, Conclusion, Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Pharmaceutical industry -- Economic aspects -- United States; Pharmaceutical industry -- Management; Knowledge management; BUSINESS & ECONOMICS / Research & Development; SCIENCE / Biotechnology; Biopharmaceutical industry; Biotechnology; Economics of industry; FDA regulations; Industrial Innovation; Regulatory reform; Strategic alliances; Electronic books